The Effect of Work Overload on Turnover Intention in Employees of Misi Pasaraya Supermarket in Barru Regency - Uhud Darmawan Natsir; Ummul Khaeriah; Zainal Ruma (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the effect of work overload towards turnover intention in employees of the Misi Pasaraya supermarket in Barru Regency. The variables that are used in this research are work overload as the dependent variable (X) and turnover intention as the independent variable (Y). Respondents that participated in this study were all employees of the Misi Pasaraya supermarket in Barru Regency, namely 50 employees. Data collection was done through distributing questionnaires. The technique that are used to analyze the research data is simple linear regression test with the help of IBM SPSS 25.00 for windows. The results that the study show is that excessive workload has a significant positive effect on exit intentions in employees of the Misi Pasaraya Supermarket in Barru Regency. The more workload the employees feel, the higher the intention of employees to leave their jobs. This is based on the results of the hypothesis test (t test) where the t-count value of 6.730 is greater than the t-table value of 2.011. While the significance value of 0.000 is much smaller than 0.05. Based on the results of the R-squared test, it can be seen that there is still a considerable proportion of variation in turnover intention, meaning that there are still other factors outside of workload that have a stronger influence in determining the intention to leave. So that work overload is not the main factor in measuring turnover intention in these supermarket employees.